2015
DOI: 10.1002/lno.10048
|View full text |Cite
|
Sign up to set email alerts
|

Natural in situ relationships suggest coral reef calcium carbonate production will decline with ocean acidification

Abstract: There are few in situ studies showing how net community calcification (G net ) of coral reefs is related to carbonate chemistry, and the studies to date have demonstrated different predicted rates of change. In this study, we measured net community production (P net ), G net , and carbonate chemistry of a reef flat at One Tree Island, Great Barrier Reef. Diurnal pCO 2 variability of 289-724 latm was driven primarily by photosynthesis and respiration. The reef flat was found to be net autotrophic, with daily pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 48 publications
8
78
2
Order By: Relevance
“…Short term BEAMS measurements demonstrated that NCC and NCP were tightly coupled over multiple days (Figure 3B), which is consistent with previous observations from various coral reefs (McMahon et al, 2013;Albright et al, 2015;Shaw et al, 2015;Takeshita et al, 2016). The NCC:NCP based on a model II regression between the two parameters was 0.21 ± 0.01, though this ratio calculated from O 2 and pH measurements is dependent on the assumed Q, and varies between 0.08 and 0.33 when Q is set equal to 0.9 and 1.1, respectively (Figure 3).…”
Section: Benthic Metabolic Ratessupporting
confidence: 91%
See 1 more Smart Citation
“…Short term BEAMS measurements demonstrated that NCC and NCP were tightly coupled over multiple days (Figure 3B), which is consistent with previous observations from various coral reefs (McMahon et al, 2013;Albright et al, 2015;Shaw et al, 2015;Takeshita et al, 2016). The NCC:NCP based on a model II regression between the two parameters was 0.21 ± 0.01, though this ratio calculated from O 2 and pH measurements is dependent on the assumed Q, and varies between 0.08 and 0.33 when Q is set equal to 0.9 and 1.1, respectively (Figure 3).…”
Section: Benthic Metabolic Ratessupporting
confidence: 91%
“…One of the challenges when making projections on how coral reefs will respond to ocean acidification on an ecosystem scale is the tightly coupled feedback between water column chemistry and benthic metabolic processes Kleypas et al, 2011;Albright et al, 2013;Andersson and Gledhill, 2013;Shaw et al, 2015;Takeshita, 2017). Coral reefs modulate the overlying seawater chemistry through two main metabolic processes: net community production (NCP) and net community calcification (NCC).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient run-off and freshwater input can influence A T , while the metabolic activity of local benthos can change pCO 2 levels. Sites in Palau (Shamberger et al, 2014;Barkley et al, 2015), Puerto Rico (Gray et al, 2012), Florida (Millero et al, 2001;Yates et al, 2007), and the GBR (Santos et al, 2011;Shaw et al, 2012Shaw et al, , 2015Kline et al, 2015) have all been characterized as having extreme in-shore low pH reef systems. In the in-shore low pH bays of Palau, coral cover and richness remained similar to control areas, but community composition shifted, with replacement of Acropora, Montipora, and Pocillopora with Porites (Barkley et al, 2015).…”
Section: Shallow In-shore Variable Reef Habitatsmentioning
confidence: 99%
“…While the experimental and statistical approaches to calculating these two relationships between P and G slightly differs, both approaches express net primary production (P) as a function of inorganic carbon flux attributed to calcification and dissolution (G) (Suzuki and Kawahata, 2003). Although the physiological mechanisms linking P and G argue for a stronger connection for P driving G (rather than the other way around; Barnes and Chalker, 1990), and it would, therefore, be more appropriate to consider G as a function of P (G/P), the majority of the literature expresses this relationship as P/G (see Shaw et al, 2015). Consequently, we express the relationship as P/G for comparative purposes.…”
Section: Introductionmentioning
confidence: 99%
“…A review of literature found that an average coral reef community exhibited a P/G slope of 4.1 when coral cover was ∼20% (Shaw et al, 2015), and suggested that a benthic coral reef community with a relatively high percent cover of calcifiers (e.g., corals and calcifying algae >20%), is associated with high rates of G (>5 mmol CaCO 3 m −2 h −1 ) relative to mean P (∼ 20 mmol C m −2 h −1 ). In this case, the community may exhibit a P/G slope approaching ∼2 (e.g., Albright et al, 2013).…”
Section: Introductionmentioning
confidence: 99%